Enhanced aridity in the source region of the Yangtze River since 5.8 ka revealed by the sediments of Saiyong Co. (10th March 2022) - Hou, Xiaohuan; Liu, Lina; Sun, Zhe; Wang, Mingda; Cao, Xianyong; Hou, Juzhi
Abstract: The Yangtze River is a major component of the 'Asian Water Tower' and it provides freshwater resources for hundreds of millions of people in East Asia. Hence, climatic and environmental changes in the source region of the Yangtze River (SRYR) are of major significance for understanding changes in the status of its freshwater resources. However, due to the contradictory results shown by the available paleoclimatic records from the SRYR and neighboring regions, it remains unclear how the regional climate and hydrology have evolved since the middle Holocene. Here, we present records of hydrological variations based on multiple proxies (grain size, scanned micro-scale X-ray fluorescence (XRF) element composition, and loss on ignition (LOI)) of the sediments of alpine lake Saiyong Co, with the aim of reconstructing hydrological changes in the SRYR since 5.8 ka. The first principal component (PC1) of the XRF scanned element record is dominated by Ti, Fe and K, representing terrigenous inputs from the catchment. The LOI profile shows an inverse pattern of variation to that of PC1, suggesting that the sedimentary organic matter is primarily derived from aquatic plants. Since 5.8 ka the overall decrease in sample scores on PC1 and the increasing LOI, together with the grain-size based lake-level record, indicate an overall drying trend in SRYR. Furthermore, several major droughts are recorded, at ∼4.0 ka, ∼2.8 ka and ∼1.8 ka. The hydrological variations at Saiyong Co are supported by multiple records from the SRYR, suggesting that millennial-scale environmental variations were regionally synchronous and were influenced by Northern Hemisphere summer insolation and movement of the intertropical convergence zone.